Program Pelatihan Desain Grafis Dan Branding Kreatif Untuk Meningkatkan Citra Bisnis Pada Umkm Sekar Handycraft Medan Tuntungan - Fadlina; Kurnia Ulfa (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
Community service program is an important thing in Higher Education which aims to implement knowledge for the community. In this case, Budidarma University is working with FKPT (Private Higher Education Cooperation Forum in North Sumatra to try to apply existing knowledge through the PKM program by holding Graphic Design Training for MSMEs. MSMEs apart from playing a role in development and economic growth, they also have a significant contribution This training program focuses on aspects of graphic design and creative branding to help improve the business image of Sekar Handicraft Micro, Small and Medium Enterprises (MSMEs) in Medan Tuntungan. The research method used is to analyze the needs of Sekar Handycraft by identifying the challenges faced by Sekar Handycraft SMEs related to graphic design and branding. Furthermore, designing creative branding training programs that suit your needs with graphic design, use of design software, logo development and branding strategies. Furthermore, it provides an in-depth understanding of how good design and strong branding can enhance the MSME business image. Furthermore, an evaluation was carried out to measure the impact on Sekar Handycraft MSMEs. includes improving product design, business image and increasing sales. The results of the evaluation show that this training program has succeeded in improving the business image of the Sekar Handycraft MSMEs. Thus, this training program not only benefits Sekar Handycraft MSMEs, but also contributes positively to the development of MSMEs in Medan Tuntungan as a whole and is a step in supporting local economic growth and improving the quality of MSME products in this area.